2010
DOI: 10.1007/s00586-010-1624-2
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Chinese version of the Oswestry disability index in patients with chronic low back pain

Abstract: The Oswestry Disability Index (ODI) is one of the most widely used questionnaires that assess disability in patients with low back pain (LBP). Responsiveness is both an important psychometric property of an instrument and a key issue for clinicians when choosing suitable outcome measures. The objective of this study was to examine the responsiveness of the Chinese version of the ODI (ODI-Chinese) for subjects with chronic LBP following a physical therapy program. In total, 76 patients with chronic LBP complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…Similar relationship between the MIC and MDC was also calculated for the English version of the MODQ in three previous studies (6 vs. 12.6) [12], (9 vs. 12.8) [34], and (5 vs. 13.1) [35]. This was also the case in several responsiveness studies of the ODQ [52,62,77]. Some studies attributed that to the anchor used for calculation, the global change scale, which could be very subjective and influenced by recall bias [62,77].…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…Similar relationship between the MIC and MDC was also calculated for the English version of the MODQ in three previous studies (6 vs. 12.6) [12], (9 vs. 12.8) [34], and (5 vs. 13.1) [35]. This was also the case in several responsiveness studies of the ODQ [52,62,77]. Some studies attributed that to the anchor used for calculation, the global change scale, which could be very subjective and influenced by recall bias [62,77].…”
Section: Plos Onesupporting
confidence: 83%
“…This was also the case in several responsiveness studies of the ODQ [52,62,77]. Some studies attributed that to the anchor used for calculation, the global change scale, which could be very subjective and influenced by recall bias [62,77]. Therefore, and since the MDC value of the Arabic-MODQ exceeds the MIC, and it is relatively well above the SEM, we suggest considering a change of more than 8 points (i.e., the MDC 95% ) after two-week of treatment as a true change in patient status [35], as described earlier in the discussion.…”
Section: Plos Onesupporting
confidence: 56%
“…A modified version of the ODI was tested in a Persian population, and tests of internal consistency and test-retest reliability, and convergent validity yielded much lower values than those of the present study (ICC=0.43-0.80, Cronbach's α=0.69, r=-0.54, p<0.001 for highest value, respectively) [27]. Studies assessing the same properties in the Korean and Chinese versions have found similar positive results [28,29]. The values obtained from the present study are quite similar to those of the aforementioned studies, supporting the finding that the PDI is a valid and reliable tool.…”
Section: Generalizabilitysupporting
confidence: 39%
“…The tool assesses 8 major domains across physical and mental health [ 39 , 40 ]. For each of the 8 domains, the items were coded, summed, and transformed into a 0–100 scale, where 0 indicates the worst health-related quality of life and a score of 100 indicates the best health-related quality of life [ 33 , 36 ]. The bodily pain subscale was reverse coded before transforming into a 0–100 scale to ensure that the higher item value indicates better health on SF-36-Am [ 41 ].…”
Section: Methodsmentioning
confidence: 99%